Characterisation by ESI FT-ICR MS of heteroatomic compounds in catalytic hydropyrolysates released from marine crude oil asphaltenes. (May 2022) - Tian, Yankuan; Jiang, Bin; Chen, Jian; Zhan, Zhao-Wen; Yang, Chao; Zou, Yan-Rong; Peng, Ping'an
Highlights: Compounds bound in four crude oil asphaltenes released by HyPy. Heteroatomic compounds in crude oils and bound-asphaltenes characterized by FT-ICR-MS. Heteroatomic compound compositions controlled by the origin of the crude oils. Reservoir secondary action can also affect heteroatomic compounds. Abstract: Aliphatic hydrocarbon biomarkers released from the asphaltene-bound fractions of crude oils have been well studied, whereas attention to released polar non-volatile heteroatomic compounds is lacking. Here, the molecular compounds bound in asphaltenes were released via catalytic hydropyrolysis (HyPy) of four crude oil samples which have two different modes of origin. The heteroatomic compounds (nitrogen, sulfur, and oxygen-bearing) in the asphaltene hydropyrolysates and crude oils were characterised by electrospray ionisation (ESI) with Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). The groups of heteroatomic compounds in the asphaltene hydropyrolysates were found to be similar to those in the free fractions of the corresponding crude oils. However, the double bond equivalents (DBE) and carbon numbers of the heteroatomic compounds were different. Generally, the composition and distribution of heteroatomic compounds in samples with different origins had different characteristics, which allowed the origins of the samples to be distinguished. However, crude oils originating from the same source rocks, did show some differences in the composition and distribution of heteroatomic compounds, reflecting differences in hydrocarbon accumulation and post-accumulation alteration. These differences were not so evident in the HyPy asphaltene fractions, indicating that the heteroatomic compounds bound in the asphaltenes can preserve original information about kerogen origins (and post diagenetic changes). Their characterisation and comparison has the potential to provide insights into their origins and into the processes of hydrocarbon accumulation and any subsequent alteration.